Choroidal and Choriocapillaris Changes after Photodynamic Therapy and Subthreshold Micropulse Laser Treatment for Central Serous Chorioretinopathy - Maria Ludovica Ruggeri; Marta Di Nicola; Marzia Passamonti; Carolina Lorenzi; Alberto Quarta; Rodolfo Mastropasqua; Lisa Toto (Medicina, 2024)
Background and Objectives: The aim of the present study is to analyze choroidal and choriocapillaris structural and functional changes in eyes affected by Central serous chorioretinopathy after Photodynamic Therapy (PDT) and Subthreshold Micropulse laser (SML) treatment. Materials and Methods: Forty-two eyes of forty-two patients were analyzed in this observational study. Twenty-four patients underwent SML treatment, whereas eighteen patients were treated with PDT. Examinations were performed at baseline and after 3 months of treatment. Main outcome measures were: Best corrected visual acuity (BCVA), central macular thickness (CMT), central choroidal thickness (CCT), pigment epithelial detachment (PED) presence and maximum height (PEDMH), and choroidal vascularity index (CVI) measured by means of Spectralis HRA + OCT (Heidelberg Engineering, Heidelberg, Germany) Optical coherence tomography (OCT) and choriocapillaris flow voids (CCFV) measured on Optical Coherence Tomography Angiography (OCT-A) platform PLEX Elite 9000 device (Carl Zeiss Meditec Inc., Dublin, CA, USA). Results: Changes in BCVA were registered in both groups over time (p < 0.001). Structural changes in terms of reduced CMT and PED presence were noted in the two groups at follow-up (p < 0.001 and p = 0.001, respectively). Structural and functional choroidal changes were found in the two groups with reduced CCT and CVI over time (p = 0.004 and p = 0.007, respectively), with significant differences between the two groups for CVI parameter (p = 0.001). CCFV increased over time in the PDT group and decreased in the SML group. Conclusions: PDT and SML are effective approaches in CSC eyes and are able to improve structural and functional parameters over time. Choroidal and choriocapillaris parameters are promising biomarkers able to monitor disease course, showing greater impact of PDT on choroid-choriocapillaris complex over time.